An optimum polyvinyl alcohol fiber length for reinforced high ductility cementitious composites based on theoretical and experimental analyses. (30th October 2020) - Ding, Cong; Guo, Liping; Chen, Bo
Highlights: ·Optimum PVA fiber length was determined based on micromechanics bridging theory. ·Dispersion state of varying length fibers were evaluated by backscattering technique. ·Effects of the fiber length on mechanical properties of HDCCs were determined. Abstract: High ductility cementitious composites (HDCCs) exhibit a robust tensile ductility accompanied by multiple cracking and a small crack width. The excellent performance of HDCCs can be elaborately designed by optimizing certain microscopic parameters. Due to the easily customized and controlled characteristics of fiber length, the aim of this study was to tailor the optimum PVA fiber length via theoretical and experimental methods. Based on the micromechanical bridging theory, the effects of the fiber length on the fiber bridging stress, the complementary energy and the fracture energy were determined. Experimental analyses including compressive tests, four-point bending tests and uniaxial tensile tests, were conducted, and five different PVA fiber lengths as 6 mm, 9 mm, 12 mm, 18 mm and 24 mm were employed in this study. Besides, the fiber dispersion properties were evaluated by a backscattering technique. The theoretical results showed that the fiber bridging stress and the complementary energy increased with increasing fiber length; however, the increasing tendency slowed as the proportion of ruptured fibers increased. The fracture energy initially increased and then decreased. A theoretical optimum fiber length was determined to be 10 mm. The experimental results showed that the compressive strength was not affected by the fiber length; the composites can achieve an optimum tensile ductility and flexural performance by incorporating PVA fibers with lengths of 9 mm, for which the fiber distribution coefficient was greater than 80%. The experimental results and theoretical analyses were basically consistent. Therefore, this research can be used as an important guide for tailoring appropriate fiber lengths for HDCC designs.